2003
DOI: 10.1046/j.1095-8649.2003.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Food habits of tilapiine cichlids of the Upper Zambezi River and floodplain during the descending phase of the hydrologic cycle

Abstract: Habitat use and diets of five tilapiine populations of the Upper Zambezi River Basin in Zambia, south‐central Africa, were examined during the 8 month descending phase of the annual hydrological cycle. All species occurred across a range of habitats, with most individuals captured from lagoons. Tilapia rendalli, a macrophyte feeder, was the only dietary specialist. Ontogenetic diet shifts were not observed over the size range examined (30–320 mm LS). Algae were uncommon in tilapiine diets. Tilapia ruweti, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 24 publications
(29 reference statements)
3
31
0
2
Order By: Relevance
“…Piscivorous cichlids (Serranochromis spp.) of the Upper Zambezi River (Africa) revealed stronger patterns of resource partitioning and niche complementarity when the water level was descending (Winemiller, 1991), and similar patterns of habitat use and dietary overlap were observed for tilapiine cichlids of the upper Zambezi (Winemiller & Kelso-Winemiller, 2003).…”
Section: Introductionmentioning
confidence: 63%
“…Piscivorous cichlids (Serranochromis spp.) of the Upper Zambezi River (Africa) revealed stronger patterns of resource partitioning and niche complementarity when the water level was descending (Winemiller, 1991), and similar patterns of habitat use and dietary overlap were observed for tilapiine cichlids of the upper Zambezi (Winemiller & Kelso-Winemiller, 2003).…”
Section: Introductionmentioning
confidence: 63%
“…Knowledge on feeding ecology of fishes and shellfishes species is of great interest both for fisheries mana- gement and aquaculture [27][28][29]. Especially in aquaculture industries, information on food habit of a species is important to formulate appropriate dry food to satisfy nutritional need for rapid growth [22,30].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies (Merron andBruton 1988, Winemiller andKelsoWinemiller 2003) indicate that Tilapia rendalli is a herbivore grazing mostly on aquatic macrophytes (and algae), however, this study showed that it occasionally feeds on fish (apart from grass, seeds, algae and detritus) corroborating Skelton (2001). O. andersonii, which was previously described as a detritivore (Merron and Bruton 1988, Skelton 2001, Winemiller and Kelso-Winemiller 2003, preyed actively on Barbus spp. in a newly inundated Lake Ngami, which had been dry for 20 years.…”
Section: Discussionmentioning
confidence: 99%